The Impact of Online Population Administration Services on Improving the Quality of Public Services - Nurfebryanti Nurfebryanti; Samsudin Samsudin; Lilis Marlina (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to examine the relationship between online-based population administration services and public service quality at the Department of Population and Civil Registration (Dukcapil) of Dompu Regency. Research Method: This research employs a quantitative approach with a descriptive-associative design. Data were collected from 100 respondents who had used population administration services in Dompu Regency within the past year. The sampling technique used was accidental sampling. Primary data were obtained through Likert-scale questionnaires, supported by observations and documentation. Data were analyzed using regression-based techniques to explore relationships among variables. Results and Discussion: The findings reveal that online-based population administration services are positively associated with public service quality. The availability of digital services improves accessibility and efficiency, although their effectiveness is influenced by system stability, officers' responsiveness, and users’ digital literacy. Implications: The study highlights the importance of strengthening technological infrastructure and improving service responsiveness. It also suggests future research to incorporate additional variables and broader methodological approaches. Originality: This study contributes by emphasizing the contextual challenges of implementing e-government services at the local level, particularly in regions with infrastructural and user-readiness limitations.